SELF-CONTROL SEBAGAI PREDIKTOR TERHADAP PERILAKU AGRESIF PADA REMAJA - Rina Rahayu Siregar (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2020)
elf-control is one of the individual internal factors that influence aggressive behavior in adolescents. This study aims to examine the effect of self-control on aggressive behavior in adolescents. This study uses a quantitative approach with an ex-post facto type. The sampling technique was purposive sampling. The research subjects were adolescents who were in high school (SMA) who had a history of committing violence. This research was conducted in D.I Yogyakarta with a total sample of 52 adolescents (27 boys and 25 girls) with an age range of 15-17 years. The data technique uses a scale of aggressive behavior and a scale of self-control. The instrument validation technique uses content validation and reliability uses the Alpha Cronbach formula. The data analysis technique used simple regression analysis. The results showed that there was a significant effect of self-control on aggressive behavior with α = 0.001 (p <0.05). Therefore, it can be ignored that self-control can be aggressive behavior among adolescents